The Klippel-Trenaunay syndrome (KTS): A case report in an infant - Muhammad Khalil Surani , Asia Noureen , Umair Khizar , Summera Tabasum , Muhammad Khalil Surani , Asia Noureen , Umair Khizar , Summera Tabasum (Journal of Rawalpindi Medical College, 2020)
Background: Klippel-Trenaunay syndrome (KTS) is a rare congenital disease having an incidence of 1/20-40,000, live births. KTS is a congenital, vascular disorder affecting usually one or rarely more than one limbs. It is characterized by port wine stain (capillary malformation), limb hemihypertrophy and other vascular anomalies. Case presentation: We present a case of this rare disorder in an infant who presented at an early stage of this disorder. The index case presented to us with a port wine stain and soft tissue edema of right lower limb. The Doppler scan showed venous malformation of right leg. The diagnosis was made on the basis of clinical and radiological criteria. Conclusion: The case is being reported in order to increase awareness among medical professionals.